Enhanced bonding strength between lithium disilicate ceramics and resin cement by multiple surface treatments after thermal cycling - Li, Rui (PLoS One, 2019)
All-ceramic restoration has become a popular technology for dental restoration; however, the relative bond strength between the ceramic and resin limits its further application. Long-term high bond strength, especially after thermal cycling, is of great importance for effective restoration. The effect of physical and/or chemical surface treatments on bonding durability is seldom reported. To overcome this problem, we investigate the bond strength between lithium disilicate ceramics (LDC) and two kinds of resin cements before and after thermal cycling for a variety of surface treatments including hydrofluoric acid, two kinds of silane and a combined effect. The shear bond strength in every group is characterized by universal mechanical testing machine averaged by sixteen-time measurements. The results show that when treated with HF and a mixed silane, the LDC surface shows maximum bonding strengths of 27.1 MPa and 23.3 MPa with two different resin cements after 5000 thermal cycling, respectively, indicating an excellent ability to resist the damage induced by cyclic expansion and contraction. This long-term high bond strength is attributed to the combined effect of micromechanical interlocking (physical bonding) and the formation of Si-O-Si and -C-C- at the interface (chemical bonding). This result offers great potential for enhancing bond strength for all-ceramic restoration by optimizing the surface treatment.